2015
DOI: 10.1007/s00192-015-2856-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of voluntary pelvic floor muscle contraction and pelvic floor muscle training on urethral closure pressures: a systematic literature review

Abstract: There is no definitive evidence that PFMT increases resting MUCP as its mechanism of action in managing SUI. The degree to which a voluntary PFM contraction augments MUCP varies widely. There was evidence to suggest PFMT increases augmented MUCP. Drawing firm conclusions was hampered by study methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
(135 reference statements)
2
26
0
2
Order By: Relevance
“…Several studies have indicated a correlation between stronger PFMs and less severity and impact of UI on quality of life. 1,2 This corresponds with our results showing that higher scores in the MOS assessed by the physiotherapist correlates with a lower score in the ICIQ-UI-SF and less UI severity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have indicated a correlation between stronger PFMs and less severity and impact of UI on quality of life. 1,2 This corresponds with our results showing that higher scores in the MOS assessed by the physiotherapist correlates with a lower score in the ICIQ-UI-SF and less UI severity.…”
Section: Discussionsupporting
confidence: 88%
“…1 However, as the pelvic floor muscles (PFMs) are invisible inside the pelvis, many women are not able to perform a correct contraction (squeeze and lift of the pelvic openings) with sufficient force to increase urethral closure pressure. 2 Hence, the women's understanding and confirmation of their ability to perform a correct PFM contraction is a prerequisite for effective PFMT. 3 In physiotherapy practices, vaginal palpation is the most commonly used method to assess, teach, and give feedback of the PFM contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of SUS has been reported in conjunction with levator ani (LA) during voluntary pelvic floor contractions and together they augment urethral closure pressure . Their relative contribution to continence and whether they can activate differentially remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…47 It has been shown that maximum urethral closure pressure increases during PFM contraction. 48 From this perspective an increase in IAP during running may be regarded positively to maintain continence.…”
Section: Discussionmentioning
confidence: 99%